Subarctic soil carbon losses after deforestation for agriculture depend on permafrost abundance - study data - Peplau, Tino; Schroeder, Julia; Gregorich, Edward; Poeplau, Christopher (Zenodo, 2022)
Contains the dataset and R code used for the study "Subarctic soil carbon losses after deforestation for agriculture depend on permafrost abundance".